Case report: Reconstruction of the left renal vein with resected autologous right renal vein interposition after excision of an inferior vena cava leiomyosarcoma - Li, Xiaohang; Li, Baifeng; Zhang, Na; Wang, Fengshan; Zhang, Chengshuo; Sun, Ning; Zhang, Jialin (Frontiers in Surgery, 2022)
Background Leiomyosarcoma of the inferior vena cava (IVC) was a rather rare disease with the characteristics of invading the adjacent viscera. Surgical resection is the only potential curative treatment, and radiation therapy and chemotherapy for leiomyosarcoma are not definite. There is few literature reporting the leiomyosarcoma of the IVC. Case presentation A previously healthy 64-year-old female was admitted to the First Affiliated Hospital of China Medical University with the complaint of right lower quadrant abdominal pain for almost three years and worsening with a radiating ache in the waist recently. Contrast-enhanced computed tomography(CT) scans revealed a large (7.8 cm*5.5 cm*5.0 cm) irregular hypodense retroperitoneal mass with heterogeneous enhancement and invasion of the IVC, and the right ureter was compressed with proximal ureteral dilatation and hydrops. Three-dimensional CT of the IVC revealed that the IVC was encircled by the tumor with moderate invasion. During the operation, the tumor was resected en bloc with the IVC (from the suprarenal to infrarenal segment), the right kidney with ureter, and the duodenum seromuscular layer. As the left renal vein was involved, it was also partly resected. IVC reconstruction was performed with the interposition of a 20 mm diameter polytetrafluoroethylene (PTFE) prosthesis, and the right renal vein was anastomosed between the left renal vein and the reconstructed IVC to guarantee the left renal vein reflux. The patient had an uneventful recovery process with normal renal function after the operation. However, follow-up CT indicated that the left renal vein was blocked two weeks after the surgery. The patient was discharged two weeks after the operation. She continues well and has no evidence of disease fourteen months after the surgery. Conclusions Wide excision of the tumor en bloc with the IVC is the main treatment for leiomyosarcoma of the IVC. IVC reconstruction with prosthetic PTFE grafts is recommended. When the left renal vein is partly resected due to involvement of the tumor, reconstruction of left renal vein should also be performed to avoid renal impairment. If the right renal vein does not show tumor involvement, the resected right renal vein can be used to reconstruct the left renal vein.